2010
DOI: 10.1111/j.1365-2966.2010.16321.x
|View full text |Cite
|
Sign up to set email alerts
|

The POINT-AGAPE survey: comparing automated searches of microlensing events towards M31

Abstract: Searching for microlensing in M31 using automated superpixel surveys raises a number of difficulties which are not present in more conventional techniques. Here we focus on the problem that the list of microlensing candidates is sensitive to the selection criteria or ‘cuts’ imposed, and some subjectivity is involved in this. Weakening the cuts will generate a longer list of microlensing candidates but with a greater fraction of spurious ones; strengthening the cuts will produce a shorter list but may exclude s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In practice, this means looking towards the very crowded stellar fields in the direction of the Galactic bulge, where stars appear so numerous that it often becomes difficult to disentangle them. However, it must be noted that the detection efficiency drops rapidly when crowding becomes so extreme that individual stars are no longer resolvable, such as when observing microlensing events in other galaxies [55][56][57].…”
Section: Blendingmentioning
confidence: 99%
“…In practice, this means looking towards the very crowded stellar fields in the direction of the Galactic bulge, where stars appear so numerous that it often becomes difficult to disentangle them. However, it must be noted that the detection efficiency drops rapidly when crowding becomes so extreme that individual stars are no longer resolvable, such as when observing microlensing events in other galaxies [55][56][57].…”
Section: Blendingmentioning
confidence: 99%
“…With data gathered from 1999 till 2001, Auriere et al [27] first announced 1 microlensing event, followed by three more by Paulin-Henriksson et al [28] and another three more by Calchi Novati et al [29]. The full POINT-AGAPE were analyzed by three working groups based at Cambridge, Zurich, and London, leading to three [30], six [31], and ten events [32] , respectively. Using the very same data-set, the Microlensing Exploration of the Galaxy and Andromeda (MEGA) presented 14 microlensing events [33].…”
Section: Introductionmentioning
confidence: 99%
“…Following AGAPE, the Pixel-lensing Observations with the Isaac Newton Telescope-Andromeda Galaxy Amplified Pixels Experiment (POINT-AGAPE) has monitored M31 from 1999 to 2001; their first microlensing event was announced in Aurière et al (2001), accompanied by three more in Paulin-Henriksson et al (2002; another 3 were reported by Calchi Novati et al (2003) with additional data from the 1.3m telescope at the MDM observatory in 1998-1999. The full POINT-AGAPE data were analyzed with 3 different pipelines based at Cambridge, Zürich, and London, where 3 (Belokurov et al 2005), 6 (Calchi Novati et al 2005), and 10 events (Tsapras et al 2010) were reported by the different nodes, respectively.…”
Section: Introductionmentioning
confidence: 99%